DFT study on the interaction between atomic aluminum and graphene - Domancich, Nicolás Fernando (2014)
In the present work, molecular orbital calculations using cluster models were performed within density functional theory (DFT) in order to study the adsorption of an Al atom on regular and defective graphene. Depending on the theoretical treatment of electronic exchange and correlations effects, different bonding results for the adsorption on the perfect surface are obtained. On the other hand, they are very similar for Al adsorbed on a carbon monovacancy. On regular graphene, the adsorption is exothermic when the Perdew, Burke and Ernzerhof (PBE) functional is used and endothermic with the Becke, 3-parameter, Lee?Yang?Parr (B3LYP) functional. Regarding the defective graphene surface, it was shown that the carbon atoms of concave angles in the vacancy are the most reactive to a radical attack. The adsorption of an Al atom on the vacancy restores the trigonal symmetry lost after the extraction of the C atom from regular graphene. Complementary calculations performed at PBE level on both regular and defective surfaces imposing periodic conditions qualitatively support the results obtained with the cluster model.